Placement and loading times in oral implantology - Padilla Avalos, César- Augusto (2022)
Oral implantology is the discipline that has revolutionized dentistry, and it is of crucial importance to carry out a practice applying clinical procedures based on scientific evidence. Likewise, multiple protocols and consensuses have been developed. That is why success lies in performing an adequate preoperative analysis (clinical and tomographic), applying solid theoretical bases and evaluating risks in each case to carry out predictable and successful treatments. This review synthesizes the indications, surgical aspects and recommendations for installation and loading times; as well as the considerations for the management of provisional restorations in oral implantology. Four times have been established for the placement of dental implants: Immediate (implant type 1), early (implants type 2 and 3) and late (implant type 4) and three times for the loading of dental implants: Immediate, early and conventional. Likewise, it is important to consider biological aspects for the proper management of perimplant tissues aimed at achieving optimal, functional and aesthetic restorations.